An analysis of incidental and symptomatic pulmonary embolism (PE) in medical oncology patients. Issue 3 (14th December 2016) - Thaker, DA; Douglas, E; Blazak, J; Xu, W; Hughes, B; Burge, M; Steinke, K; Wyld, D
Abstract: Aim: To determine the incidence of symptomatic versus incidental pulmonary embolism (PE) in oncology patients, characterize the nature and extent of incidental PE and the factors contributing to diagnosis. Methods: Specialized web search engine was used to identify oncology patients with positive imaging studies for PE. PE identified at staging CT scans were classified as incidental PEs, whereas PE diagnosed by CTPA/VQ scan were classified as symptomatic PEs. Results: A total of 111 patients with PE were identified over the period of three years. Of these, 67 (60%) patients had symptomatic whereas 44 (40%) patients had incidental PE. Most PEs were segmental and non‐occlusive irrespective of the type of PE or stage of the disease. Incidence of PE was equal with/without chemotherapy. Platinum‐based chemotherapy was more commonly associated with PE. Most patients received anticoagulation irrespective of type of PE. Conclusion: Forty percent of the diagnosed PEs were incidental, more common in the metastatic group. This may be due to the increased frequency of staging scans performed in patients with metastatic disease, as well as the inherent disease biology of metastatic compared with localized disease. Further prospective analysis of survival by PE subtype and optimal length of anticoagulation in incidental PE is warranted.